REDESIGN UI/UX BANK PLASTIK MENGGUNAKAN METODE USER CENTERED DESIGN - Aziza, Fakhita Nur; Angriani, Husni; Thayf, Mohammad Sofyan S. (JTRISTE, 2025)
"Bank Plastik" is an application that facilitates the exchange of plastic waste for money. The results of a user experience survey for the Bank Plastik application indicated several areas that require improvement, one of which is the UI/UX design. To validate the survey results, a first-stage testing was conducted to determine whether a redesign of the Bank Plastik application is necessary. Based on the first-stage testing, the original design received a score of 50.8, indicating that the score falls in the "poor" category and is below the standard SUS (System Usability Scale) score of 53. Therefore, a redesign of the UI/UX of the Bank Plastik application is deemed necessary. The User Centered Design method was employed to carry out the redesign of the Bank Plastik UI/UX to enhance the user experience when using the application. The results of the User Centered Design implementation, using the task success metric, revealed issues with tasks 1 and 2. The findings from the time on task metric showed that respondents were able to complete all tasks but faced challenges with the slide slogan page. Respondents two and five experienced delays more frequently compared to other respondents. The testing of the error metric yielded an average error rate for each task of 16% across all respondents. The results of the second stage testing demonstrated that the satisfaction score for the redesign was higher than that of the original design in the first stage, with a redesign score of 75.5, indicating an "excellent" level of satisfaction. In conclusion, based on the survey and testing results, it is clear that a redesign of the Bank Plastik application's UI/UX has been successful in improving the user experience.